2003
DOI: 10.1016/s0042-6822(03)00284-8
|View full text |Cite
|
Sign up to set email alerts
|

The coat protein of prunus necrotic ringspot virus specifically binds to and regulates the conformation of its genomic RNA

Abstract: Binding of coat protein (CP) to the 3' nontranslated region (3'-NTR) of viral RNAs is a crucial requirement to establish the infection of Alfamo- and Ilarviruses. In vitro binding properties of the Prunus necrotic ringspot ilarvirus (PNRSV) CP to the 3'-NTR of its genomic RNA using purified E. coli- expressed CP and different synthetic peptides corresponding to a 26-residue sequence near the N-terminus were investigated by electrophoretic mobility shift assays. PNRSV CP bound to, at least, three different site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 45 publications
2
51
0
6
Order By: Relevance
“…Addition of Hfq hexamer to a 1:2 RprA:Hfq stoichiometric ratio, showed only a small further decrease in ellipticity (0.46 Δε to 0.37 Δε) (Fig. 4A), which may be more indicative of a slight chromophore rearrangement upon Hfq binding, rather than a significant structural change (Aparicio et al 2003;Vincent et al 2012b;Henderson et al 2013). For OxyS, the addition of Hfq hexamer to a 1:1 stoichiometric ratio reduced the ellipticity at 265 nm by 35% (1.00 Δε to 0.65 Δε) (Fig.…”
Section: Hfq Changes the Structure Of Oxys And Rpramentioning
confidence: 95%
See 2 more Smart Citations
“…Addition of Hfq hexamer to a 1:2 RprA:Hfq stoichiometric ratio, showed only a small further decrease in ellipticity (0.46 Δε to 0.37 Δε) (Fig. 4A), which may be more indicative of a slight chromophore rearrangement upon Hfq binding, rather than a significant structural change (Aparicio et al 2003;Vincent et al 2012b;Henderson et al 2013). For OxyS, the addition of Hfq hexamer to a 1:1 stoichiometric ratio reduced the ellipticity at 265 nm by 35% (1.00 Δε to 0.65 Δε) (Fig.…”
Section: Hfq Changes the Structure Of Oxys And Rpramentioning
confidence: 95%
“…1A,B). Furthermore, like RprA, the addition of Hfq hexamer to a 1:2 OxyS:Hfq stoichiometric ratio showed only a small further decrease in ellipticity at 265 nm (0.65 Δε to 0.60 Δε), suggestive more of a binding rearrangement rather than further structural change (Aparicio et al 2003;Vincent et al 2012b;Henderson et al 2013).…”
Section: Hfq Changes the Structure Of Oxys And Rpramentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 9 highlights that CP dimerization region (DR) was less conserved than RNA-binding domain (RBD). The PNRSV CP has the capacity to bind to the 3'UTR of its RNA3 and 4 [58,59] through an RNA-binding domain (RBD) rich in R residues located at the N-terminal region between amino acid residues 25 to 50 of the protein [59,60]. RBD is necessary for different viral processes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Putative zinc-finger domains have also been found in case of ApMV and PNRSV [1,14,15,28]. In case of PNRSV CP 26 amino acid region located in between amino acids 25-50 from the N-terminal end represented as RNA binding domain and thus involved in genome activation [5]. Since it has been already proved that N-terminus of PNRSV CP is required for RNA binding, Present finding also showed that N-terminus might also be involved in protein-protein interaction during capsid formation whereas C-terminus is the most important for dimer formation.…”
Section: Discussionmentioning
confidence: 99%